On the Logic of Verbal Modification - Beaver, David; Condoravdi, Cleo (Proceedings of the Amsterdam Colloquium, 2007)
We describe Linking Semantics, providing a uniform compositional analysis of argument-dropping inferences, quantifier scope, and temporal modification.